2005
DOI: 10.1167/iovs.04-0430
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Fundus Autofluorescence Patterns in Early Age-Related Macular Disease

Abstract: Various phenotypic patterns of abnormal FAF can be identified with cSLO imaging. Distinct patterns may reflect heterogeneity at a cellular and molecular level in contrast to a nonspecific aging process. The results indicate that the classification system yields a relatively high degree of intra- and interobserver agreement. It may be applicable for determination of novel prognostic determinants in longitudinal natural history studies, for identification of genetic risk factors, and for monitoring of future the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
200
2
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(215 citation statements)
references
References 31 publications
7
200
2
6
Order By: Relevance
“…8,9 Several studies concluded that FAF imaging in dry ARMD does not necessarily correspond to the fundus changes observed, yet provides information over and above the normal fundus photography methods used. 8,10 Active stages of acute central serous retinopathy (CSR) show an increase in FAF corresponding to increased metabolic activity of the retinal pigment epithelium (RPE), while chronic CSR shows decreased FAF probably due to the reduced metabolic activity of the RPE secondary to photoreceptor cell loss. 11 In pseudoxanthoma elasticum and atrophic ARMD, atrophy of the RPE is associated with decreased FAF.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Several studies concluded that FAF imaging in dry ARMD does not necessarily correspond to the fundus changes observed, yet provides information over and above the normal fundus photography methods used. 8,10 Active stages of acute central serous retinopathy (CSR) show an increase in FAF corresponding to increased metabolic activity of the retinal pigment epithelium (RPE), while chronic CSR shows decreased FAF probably due to the reduced metabolic activity of the RPE secondary to photoreceptor cell loss. 11 In pseudoxanthoma elasticum and atrophic ARMD, atrophy of the RPE is associated with decreased FAF.…”
Section: Introductionmentioning
confidence: 99%
“…The peri-lesion hyperfluorescence observed in exudative wet AMD is lower than that observed in classic wet AMD. FAF usually increases in various diseases, leading to disordered RPE metabolism and the accumulation of lipofuscin, followed by increased fluorescence (Bindewald et al, 2005a). The high fluorescence signal at the edge of CNV lesions indicates that the accumulation of lipofuscin is significant.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with advanced AMD, the diffuse and banded FAF patterns in the junctional zone of GA appear to be precursors to expansion. 18,52,72 Newer studies investigating the association between reticular drusen, reticular FAF pattern, and advanced AMD indicate that reticular macular disease is another important risk factor for disease progression. as small as 2 μm.…”
Section: Autofluorescencementioning
confidence: 99%